2018
DOI: 10.1021/acs.langmuir.8b00497
|View full text |Cite
|
Sign up to set email alerts
|

Light-Switchable Self-Assembly of Non-Photoresponsive Gold Nanoparticles

Abstract: Herein, an interesting light-induced self-assembly behavior from non-photoresponsive gold nanoparticles (Au NPs) was reported. Specifically, a pH-responsive amphiphile SPBwas developed that contained a particular phenylboronic acid moiety and showed excellent surface activity at the neutral and basic conditions, thereby stabilizing Au NPs well. Accordingly, the SPB-functionalized Au NPs showed strong pH dependence that there presented the pH-induced reversible self-assembly behavior. Furthermore, the introduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 60 publications
(94 reference statements)
0
18
0
Order By: Relevance
“…It also bears great synthetic potential for the formation of versatile, switchable, and functional nanostructures [ 2 , 3 , 4 , 5 ]. Noncovalent interactions can be triggered by external influences, such as the change of pH [ 6 , 7 , 8 , 9 ], light irradiation [ 10 , 11 , 12 , 13 , 14 ], thermal activation [ 15 , 16 , 17 , 18 ], introduction of a magnetic field [ 19 , 20 , 21 ], moisture, or redox response [ 22 , 23 , 24 , 25 ]. Of high interest are light-responsive systems, for example in the fields of sensors [ 26 , 27 , 28 ] or therapy [ 29 , 30 , 31 ], and, thus, it is desirable to explore novel concepts toward light-triggerable self-assembly.…”
Section: Introductionmentioning
confidence: 99%
“…It also bears great synthetic potential for the formation of versatile, switchable, and functional nanostructures [ 2 , 3 , 4 , 5 ]. Noncovalent interactions can be triggered by external influences, such as the change of pH [ 6 , 7 , 8 , 9 ], light irradiation [ 10 , 11 , 12 , 13 , 14 ], thermal activation [ 15 , 16 , 17 , 18 ], introduction of a magnetic field [ 19 , 20 , 21 ], moisture, or redox response [ 22 , 23 , 24 , 25 ]. Of high interest are light-responsive systems, for example in the fields of sensors [ 26 , 27 , 28 ] or therapy [ 29 , 30 , 31 ], and, thus, it is desirable to explore novel concepts toward light-triggerable self-assembly.…”
Section: Introductionmentioning
confidence: 99%
“…The developed NP-polymer complexes demonstrated pH-induced reversible self-assembly behavior, however, the introduction of photo-acid generator (diphenyliodonium) changed self-assembly behavior induced by light. [164] An external electric field can maintain the assembled state of the NP-polymer complexes. Montelango et al reported on the implementation of electrotunable liquid mirror based on voltage-controlled self-assembly of mercaptopropanesulfonate-stabilized 16 nm Au NPs at the interface between two immiscible electrolytes.…”
Section: Recent Examples Of Self-assembled Nanomaterialsmentioning
confidence: 99%
“…The developed NP‐polymer complexes demonstrated pH‐induced reversible self‐assembly behavior, however, the introduction of photo‐acid generator (diphenyliodonium) changed self‐assembly behavior induced by light. [ 164 ] An external electric field can maintain the assembled state of the NP‐polymer complexes. Montelango et al.…”
Section: Adaptive Self‐assembled Nanomaterialsmentioning
confidence: 99%
“…In Section , we discussed examples of the reversible self‐assembly of non‐photoswitchable NPs in light‐responsive media. Li and co‐workers designed a light‐responsive medium capable of decreasing the pH irreversibly, thus inducing the formation of permanent NP aggregates . For the photosensitive component of the light‐responsive medium, these researchers used a solution of a commercially available, water‐soluble photoacid generator, diphenyliodonium nitrate.…”
Section: Irreversible Self‐assembly Of Nanoparticlesmentioning
confidence: 99%